Biomarkers for prediction and diagnostics of preeclampsia - O. V. Radkov; L. N. Korichkina; O. V. Sizova; Y. V. Volf; E. K. Paramonova (Acta Biomedica Scientifica, 2018)
Preeclampsia (PE) is a life-threatening complication of pregnancy associated with a high rate of maternal and perinatal morbidity and/or mortality. This study was aimed at evaluation of total and fetal cell-free DNA (cftDNA and cffDNA) in maternal plasma to assess whether this could represent a reliable predictive marker of early, late PE and whether intrauterine growth restriction (IUGR) as seen in PE is associated with levels of cell-free DNA. Diagnostic criteria for fetal growth retardation are calculated from the results of blood test results obtained in 26-36 weeks of gestation. We performed a PCR assay to compare the cftDNA and cffDNA concentration in maternal plasma among 3 groups of pregnant women. These included 119 women with overt PE (47 - early PE, 72 - late PE), 24 women at risk for the disease who developed PE (8 -early PE, 16 - late PE), and 30 controls. CffDNA quantification is a promising marker for early preeclampsia prediction. Cut-off value of 0,87 ng/ml for cffDNA (87.5 % sensitivity and 66,67 % specificity). Since the increase in cftDNA and cffDNA seems to be related to the presence IUGR in pregnancies which are complicated with early PE. Thus, it suggests that cftDNA and cffDNA could represent a potential biomarker of IUGR among individuals with early PE.